LATE-HOLOCENE VEGETATION AND FIRE HISTORY FROM FERRY LAKE, NORTHWESTERN WISCONSIN, USA - Lynch E.A.; Calcote R.; Hotchkiss S. (My University, 2006)
We used charcoal and fossil pollen to investigate how fire, vegetation and climate have interacted over the past 2300 years at Ferry Lake, located on a sand plain in northwestern Wisconsin. Pollen analysis shows a rapid transition from oak (Quercus spp.)-dominated woodland to a relatively open pine (Pinus spp.) forest at 1450 cal. yr BP, and a more closed-canopy pine forest beginning about 700 cal. yr BP. We calculated accumulation rates of 125-250 Um charcoal fragments (CHAR) in contiguous 0.5 cm thick sediment samples, each representing 7-10 years. Graminoid charcoal fragments were tallied separately to track the relative abundance of grass charcoal. During the oak period charcoal peaks have relatively weak periodicity and relatively high accumulation rates of grass charcoal. Charcoal peaks are less frequent (with a periodicity of 130-200 years), and larger during the open-canopy pine period, with lower grass CHAR. CHAR of both charcoal types decreases further between 1000 and 850 cal. yr BP and remains low until the period of European settlement. Several hundred years later (700 cal. yr BP) white pine pollen increases and pollen from herbaceous taxa decreases, suggesting a more mesic, closed-canopy forest. Our results demonstrate that the vegetation and fire regime at this sandplain site changed substantially, but apparently not synchronously, during the last 2300 years, a period when millennial-scale regional climate was relatively similar to modern.
Keywords: CHARCOAL ANALYSIS; CLIMATE CHANGE; FIRE HISTORY; POLLEN; PALAEOECOLOGY; PINE BARRENS; LATE HOLOCENE; WISCONSIN; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен